Outcomes of HeartMate 3 in pediatric patients with end-stage heart failure: a single-center preliminary experience from Turkey - Doğan, Eser; Ulger Tutar, Zulal; Tuncer, Osman Nuri; Levent, Reşit E.; Engin, Çağatay; Yağdı, Tahir; Atay, Yüksel; Özbaran, Mustafa (Frontiers in Cardiovascular Medicine, 2024)
Objectives We aim to evaluate our initial experience with the HeartMate 3 (HM3) device (Abbott, USA) for palliating pediatric patients with end−stage heart failure (ESHF). Methods We conducted a retrospective review of clinical data from pediatric patients (aged 7–18 years) who underwent HM3 implantation for ESHF at our institution between 2022 and 2024. Patient demographics and follow−up data were comprehensively analyzed. Results We identified 11 patients (45% males) with a median age of 14 years (IQR 11–17), a median weight of 47 kg (IQR 28–50), a median height of 159 cm (IQR 135–165), and a median body surface area of 1.36 m2 (IQR 1.07–1.53) at the time of the intervention. All patients were diagnosed with dilated cardiomyopathy and categorized with PEDIMACS profiles ranging from one to three. The median ICU stay was 14 days (IQR 6–32), with 11 patients receiving inotropic support for a median of four postoperative days (IQR 3–8). The median follow−up period was 150 days (IQR 90–210). Early complications included two cases of pleural effusion, 1 case of cardiac tamponade, 3 cases of polyuria, and one instance of positive blood cultures. One patient, who was non−compliant with warfarin therapy, developed a thrombus in the right atrium that was resolved with a revision of anticoagulant therapy, and did not experience pump thrombosis. During follow−up, one patient died after 28 days from sepsis, one underwent heart transplantation after 10 days, and nine patients remained alive on the device. Notably, there were no reported cases of pump thrombosis, ischemia, or stroke post− implantation. Conclusions The HM3 device appears to be a safe and effective palliative option for pediatric patients with ESHF.